2022
DOI: 10.3390/v14020273
|View full text |Cite
|
Sign up to set email alerts
|

High Level of Pre-Treatment HIV-1 Drug Resistance and Its Association with HLA Class I-Mediated Restriction in the Pumwani Sex Worker Cohort

Abstract: Background: We analyzed the prevalence of pre-antiretroviral therapy (ART) drug resistance mutations (DRMs) in a Kenyan population. We also examined whether host HLA class I genes influence the development of pre-ART DRMs. Methods: The HIV-1 proviral DNAs were amplified from blood samples of 266 ART-naïve women from the Pumwani Sex Worker cohort of Nairobi, Kenya using a nested PCR method. The amplified HIV genomes were sequenced using next-generation sequencing technology. The prevalence of pre-ART DRMs was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…A recent study on the oldest FSW cohort, Pumwani, found a high level of PDR (38%) across all ART classes. [ 9 ] A systematic review of 332 datasets with 63,111 subjects focusing on key populations found that the pooled prevalence estimate of any PDR was high among men who have sex with men at 13.0% (95% CI: 11.0–14.0), and sex workers at 17.0% (95% CI: 6.0–32.0), but lower among injecting drug users at 7.0% (95% CI: 5.0–10.0). [ 10 ] Of concern is the rise in PDR in the general population to non-nucleoside reverse transcriptase inhibitors (NNRTIs) after the ART scale-up, with substantial increases in resistance to NNRTI in East Africa (36%, 95% CI: 21–52) and southern Africa (23% 95% CI: 7–42).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study on the oldest FSW cohort, Pumwani, found a high level of PDR (38%) across all ART classes. [ 9 ] A systematic review of 332 datasets with 63,111 subjects focusing on key populations found that the pooled prevalence estimate of any PDR was high among men who have sex with men at 13.0% (95% CI: 11.0–14.0), and sex workers at 17.0% (95% CI: 6.0–32.0), but lower among injecting drug users at 7.0% (95% CI: 5.0–10.0). [ 10 ] Of concern is the rise in PDR in the general population to non-nucleoside reverse transcriptase inhibitors (NNRTIs) after the ART scale-up, with substantial increases in resistance to NNRTI in East Africa (36%, 95% CI: 21–52) and southern Africa (23% 95% CI: 7–42).…”
Section: Introductionmentioning
confidence: 99%
“…Willim et al [23] analyzed the prevalence of pre-antiretroviral therapy (ART) drug resistance mutations (DRMs) in a Kenyan population and observed high levels of HIV drug resistance against all classes of antiretroviral drugs, including the current first-line ART regimens in Africa. The authors also detected some correlation between DRMs and host HLA class I genes and suggested that the development of DRMs may be influenced by HLA class I-restricted immunity.…”
mentioning
confidence: 99%